Foreign Investments and Institutional Convergence in Southeastern Europe - Eleni A. Kaditi (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
Foreign investments are in the focus of most governments around the world. In order to be able to set a policy agenda which is successful in promoting FDI, it is necessary to understand their detfirminants. This paper examines whether and to what extent sound institutions and the degree of regulation deter or attract FDI flows in four economies of Southeastern Europe. In a dynamic panel analysis, a broad set of institutional and regulatory variables that may affect the decision of foreign investors to undertake investment projects in this region is examined, using firm-level data. Analysis shows that the quality of the institutional environment significantly influences foreign capital. Governments in this region should, therefore, focus primarily on creating a good legal system, having relatively stable political and economic conditions.
Keywords: F23; D73; P3; 330; Foreign Investments; Corruption; Transition Economies; Direktinvestition; Korruption; Institutionelle Infrastruktur; Transformationsstaaten; Südosteuropa